Қарақалпақ халқының батырлары минген тулпарлар ҳаққында - Оразымбетов, Е.К (SCIENCE and SOCIETY, 2024)
The article describes the characteristics of the horses that the Karakalpak heroes rode, their loyalty, friendship and their place in the education of youth from a pedagogical point of view.
Keywords: zhuirik; kanazat; argymak; horse; warriors; loyalty